Synthesis of Porous Carbon-Supported Copper-Based Electrocatalysts Derived from IRMOF: A Non-Noble Metal Electrocatalyst with Optimized Active Sites for the Oxygen Evolution Reaction. Issue 5 (1st May 2022) - Parkash, Anand; Solangi, Nizamuddin; Solangi, Sorath; Almani, Sikandar; Soomro, Suhail Ahmed
Abstract : Metal-organic frameworks (MOFs) are a type of porous material that offers a highly flexible medium for future broad application due to their crystallinity, structural diversity, and permanent porosity. Herein, by doping copper with Isoreticular metal-organic framework-3 (IRMOF-3) as a precursor, an effective electrocatalyst with x%Cu/IRMOF-3 (x = 1%–10%) porous carbon spheres were prepared and characterized. The oxygen evolution reaction (OER) electrocatalytic properties of x%Cu/IRMOF-3 were investigated. According to the findings, 5%Cu/IRMOF-3–900 has a superior performance with a low overpotential of 265 mV and strong long-term stability in alkaline solution. With a porous structure and high nitrogen content, 5%Cu doped IRMOF-3 is superior to several reported precious metal-free electrocatalysts developed of MOFs. In this research, MOF has been utilized as a template to design a new approach for developing non-noble metal OER catalysts.